Carboxyferrocene modulated Ni/Co bimetallic metal-organic framework for highly efficient electrocatalysis of urea oxidation reaction. (1st October 2022) - Xu, Liqiang; Wang, Xinxing; Zhang, Li; Sun, Haodi; Xie, Xiaopei; Zhang, Yubing; Tan, Boyu; Yuan, Ruoyu
Highlights: NiCoMOF-Fc was simply prepared by defect engineering and metal node engineering. The introduction of Fc altered the coordination environment of Ni active sites. The electrical conductivity of NiMOF-Fc was also improved thanks to the Fc. The electronic structure of Ni active sites was further optimized by doping Co 2+ . The NiCoMOF-Fc can be directly adopted as highly efficient UOR electrocatalysts. Abstract: Metal-organic frameworks (MOFs) have shown unique advantages and huge potential in heterogeneous catalysis such as photocatalysis due to their impressive physicochemical properties. However, the direct application in electrocatalysis are usually limited by their poor electrocatalysis performance. Herein, we present the synthesis of Ni/Co bimetallic organic framework with missing linkers of carboxyferrocene (NiCoMOF-Fc) on nickel foam (NF) by a facile protocol of one-step solvothermal method for the urea oxidation reaction (UOR) electrocatalysis. The integration of defect tailoring and bimetallic coupling effect changes the coordination environment of Ni active sites and optimizes the electronic structure, which significantly improves the electrocatalytic activity of the Ni-based MOF. The NiCoMOF-Fc modified NF exhibits excellent electrocatalytic performance towards UOR with high current density at low potential (140 mA cm −2 at 1.299 V vs. RHE and 782 mA cm −2 at 1.5 V vs. RHE), a small Tafel slope of 46.2 mV dec −1 and good durability. In addition, a two-electrode electrolyser with NiCoMOF-Fc as the bifunctional catalyst for UOR and hydrogen evolution reaction (HER) has also been successfully constructed, which shows bright prospect of practical use. Graphical abstract: Image, graphical abstract .